Childs' canonical approach: a critical assessment - Brown, Robert G. (Studies in biblical literature, 2023)
"How should Christians read the Bible to learn about God? This is a perennial issue in Christianity and a variety of answers have of course been given over time. Perhaps the most profound answer to this question in the twentieth century came from Brevard S. Childs, an Old Testament professor, whose 'canonical approach' sought to redefine how the Bible is used in the Church. Childs' Canonical Approach: A Critical Assessment provides a fresh study of Childs' approach from the perspective of biblical studies. It makes two arguments that break new ground. Firstly, it argues that Childs' approach consists of three main elements that were variously developed and implemented over time: the theory of canonical shaping; the prioritisation of the canonical texts; the search for the Bible's subject matter. Secondly, it argues that, though rich and informed, these elements are ultimately unjustifiable and thus that the canonical approach is a failure. This Book provides an insightful contribution to the ongoing academic debate on Childs' canonical approach. It is also an excellent primer for students interested in Childs, or who are generally considering how to read the Bible theologically"--